2021
DOI: 10.3390/biom11121746
|View full text |Cite
|
Sign up to set email alerts
|

Altered Steroidome in Women with Gestational Diabetes Mellitus: Focus on Neuroactive and Immunomodulatory Steroids from the 24th Week of Pregnancy to Labor

Abstract: Gestational diabetes mellitus (GDM) is a complication in pregnancy, but studies focused on the steroidome in patients with GDM are not available in the public domain. This article evaluates the steroidome in GDM+ and GDM− women and its changes from 24 weeks (± of gestation) to labor. The study included GDM+ (n = 44) and GDM− women (n = 33), in weeks 24–28, 30–36 of gestation and at labor and mixed umbilical blood after delivery. Steroidomic data (101 steroids quantified by GC-MS/MS) support the concept that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…Our study confirmed elevated serum DHEA, T, and A4 levels in women with GDM. However, a latest study reveals that serum T and E2 levels is reduced with the increasing of gestational age, while DHEA, A4 and E1 were found to be unrelated to GDM ( 33 ). This finding goes against our work.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our study confirmed elevated serum DHEA, T, and A4 levels in women with GDM. However, a latest study reveals that serum T and E2 levels is reduced with the increasing of gestational age, while DHEA, A4 and E1 were found to be unrelated to GDM ( 33 ). This finding goes against our work.…”
Section: Discussionmentioning
confidence: 98%
“…Aromatase knockout mice have decreased E2 levels, accompanied by reduced glucose oxidation, elevated adiposity, and insulin levels ( 44 , 45 ). E2 is an important antidiabetic steroid operating via binding to nuclear receptors as well as via modulation of ion channels controlling the secretion of pancreatic hormones ( 33 , 46 ). Therefore, E2 deficiency in GDM women with overweight may be an important component participating in the pathophysiology of GDM.…”
Section: Discussionmentioning
confidence: 99%